2017
DOI: 10.18632/oncotarget.16139
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of mitral valve abnormalities in left atrial myxoma patients using cardiac CT

Abstract: BackgroundTo retrospectively evaluate mitral valve abnormality in left atrial myxoma patients by using cardiac computed tomography (CT).Material and methodsCardiac CT was performed in 56 patients with left atrial myxoma and 50 controls. Tumor and mitral valve characteristics were analyzed. The mitral valve parameters differences were compared between patients with myxoma and controls, myxoma with or without mitral valve obstruction, different obstruction degrees, respectively. Receiver operating characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrary, most of the MR cases remained complicated with regurgitation post-operatively even with additional mitral valve repair or replacement procedure. 14,15 Our patient recovered substantially post-operative with residual MR without any further mitral intervention intra-operatively.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrary, most of the MR cases remained complicated with regurgitation post-operatively even with additional mitral valve repair or replacement procedure. 14,15 Our patient recovered substantially post-operative with residual MR without any further mitral intervention intra-operatively.…”
Section: Discussionmentioning
confidence: 73%
“…Valvular regurgitation and cardiac arrhythmias remain as the most common post-operative complication, followed by delayed sternal wound healing, rarely pericardial effusion and pneumothorax. 2,14 Pre-operatively, left-sided cardiac myxoma commonly causes mitral stenosis (66.1%) by obstructing the outflow tract followed by mitral regurgitation (33.9%), postulated to be caused by the dilation of the mitral annulus. All cases with mitral stenosis recovered post-excision of myxoma.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, preoperative imaging studies have shown that the mitral annulus may be enlarged in some patients with myxoma. 3 This may result either from mechanical stretching of the valve and annulus by tumor protrusion or as a compensatory change to increase effective valve orifice to accommodate blood flow across the mitral valve obstructed by the tumor. In this issue of the Journal, Blanco and colleagues 4 elegantly report another interesting mechanism of mitral regurgitation.…”
mentioning
confidence: 99%